Dissecting domain-specific functions of the IGF2/M6P receptor - Can, S (2016)
The P-type lectin Mannose 6-phosphate/Insulin-like growth factor 2 receptor (M6P/IGF2R) is a type I trans-membrane protein with 15 homologous extracellular domains that bind several ligands. While domains 3, 5 and 9 bind to Mannose 6-Phosphate (M6P), domain 11 binds to IGF2 (Insulin-like growth factor 2). In mice, igf2r expression is monoallelic and full knock-out of the receptor maternal allele (Igf2r-m/+p) results in developmental abnormalities and neonatal lethality, marking the significance of the receptor in organogenesis and postnatal viability. What remains unknown is the contribution of each of these domains into M6P/IGF2R's roles in development. My aims are dissecting M6P and IGF2 binding domains' functions in the context of full length receptor in vitro and investigating Domain 11 loss-of-function in vivo. In this thesis, SPR analysis of full-length M6P/IG2R mutants showed that M6P binding domains function independent of each other, and domain 3 is the dominant M6P binding domain at physiological pH. Introducing gain-of-function mutations to domain 11 binding site revealed presence of inter-loop interactions and inhibitory residues in CD and FG loop in the context of the full-length receptor. I1572A results in domain 11 loss of-function mutation with preserved binding of other ligands, suggesting that I1572A (or its homolog mutations in other mammals) could be utilized in in vivo studies to dissect domain 11 functions. In mice, maternal transmission of Domain 11 loss-of-binding function mutation (I1565A, mouse homolog of I1572A) resulted in increased birth weight and substantially reduced postnatal survival (~30%). The disproportional cardiomegaly and disorganised myocardium in Igf2rI1565Am/+p neonates suggest that postnatal lethality is due to cardiac insufficiency. Furthermore, placental and embryonic oedema in Igf2rI1565Am/+p mice is indicative of the presence of prenatal congestive cardiac failure, beginning as early as at embryonic day 14.5. In addition, surviving females developed uterine distension due to vaginal atresia. Overall, these results show that domain 11 loss-of-function, on its own, is the primary reason for the most of abnormalities that is previously reported in the full knock out mice. Thus, domain 11 is the primary domain for M6P/IGF2R’s roles in development.